THE MYTH OF FEMALE BEAUTY: STUDY OF REPRESENTATION TOWARD POST-NEW ORDER NOVELS WRITTEN BY MALES - Lelu Dina Apristia (Sanata Dharma University, 2019)
Males representing female beauty without experiencing to be real females in post-New Order era become the background of this study. This study is aimed: (1) to identify female beauty in post-New Order era represented by male writers, (2) to identify factors forming the representation. To achieve the aims, the study is done by applying Stuart Hall's representation theory which is not only about meaning produced through language and knowledge produced through discourse, but also about revealing patriarchal structure containing in discourse. After applying Stuart Hall's representation theory, it is found that female beauty in post-New Order era is not the same as the one in New Order era. Male writers represent that beautiful females in post-New Order are the ones whose body attracting other people and who struggle for freedom. The representation is formed by male writers in relation with males in post-New Order era and in discursive formation in post-New Order siding with males to keep masculine domination.